Electrically Conducting Pullulan-Based Nanobiocomposites Using Carbon Nanotubes and TEMPO Cellulose Nanofibril - Sabina Yeasmin; Jeong Hyun Yeum; Byung Chul Ji; Jin Hyun Choi; Seong Baek Yang (Nanomaterials, 2021)
Hybrid nanobiocomposite films are prepared using a solution casting by incorporating TEMPO cellulose nanofibrils (TOCNs) and carbon nanotubes (CNTs) into an aqueous solution of pullulan (PULL). The presence of CNT is confirmed by XRD characterization, and the prepared film shows an increased degree of crystallinity after the addition of TOCNs and CNT. The maximum degree of crystallinity value is obtained for CNT 0.5 % (59.64%). According to the Fourier-transform infrared spectroscopy, the shifts of the characteristic -OH peak of PULL occurred after the addition of TOCNs and aqueous CNT (3306.39 to 3246.90 cm−1), confirming interaction between the TOCNs, CNTs, and PULL matrix. The prepared films show enhanced material properties including higher tensile strength (65.41 MPa at low CNT content (0.5%)), water barrier properties, and reduced moisture susceptibility (5 wt.% CNT shows the lowest value (11.28%)) compared with the neat PULL film. Additionally, the prepared films are almost biodegradable within 64 days and show excellent electrical conductivity (0.001 to 0.015 S/mm for 0.5–5% CNT), which suggests a new approach to transform natural polymers into novel advanced materials for use in the fields of biosensing and electronics.